Public Leadership in Times of Crisis: Lessons from the Covid-19 Pandemic in Malaysia - Benlahcene, Abderrahmane; Abdullah, Nurfarhana Salihah (2020)
Leaders at all levels of government are put into the test during times of crisis, uncertainty, and collective stress. The current regional and global Covid-19 crisis, which exerts immense economic and social challenges on various sectors offers an opportunity for a careful analysis of the performance of our leaders in times of crisis. The purpose of this paper is to evaluate different tasks associated with the performance of public leadership during the Covid-19 pandemic in the Malaysian context. The focus of this evaluation is on five tasks during the ongoing crisis, namely: Early recognition, Sense-making, Making critical decisions, Cooperation, and Communication. In doing so, this paper provides valuable insights on crisis management for public leaders and policy-makers within the region.